Sexual difference without cisness in Ulysses. Issue 2 (1st February 2022) - Heaney, Emma
ABSTRACT: Are bodies divided into two mutually exclusive sexes whose structures determine the consciousness of those that inhabit one or the other kind of body? James Joyce's Ulysses offers a story of bodies that don't work this way and nonetheless exist in the social world. This chapter addresses the episodes in the novel in which the physical structures of the bodies that are used to assign sex thrust upon the characters that possess them sensations that don't align neatly with the sexed experiences that supposedly emanate from them. Put otherwise, in these moments, the novel puts the lie to the naturalness of cisness. This textual practice, however, doesn't suggest that simply recognising that sexed structures don't naturally or eternally determine sexed experiences does not mean that this connection can be easily overthrown. The characters in fact remain mired in sexual difference, the social structure that denies the ideological status of cisness. This essay engages with Joyce's distinction between cisness and sexual difference in order to understand the quintessentially Freudian tone of melancholia that envelops these characters whose bodies produce empirical sensations that cut through the ideology of sex.